Pectus deformities: tomographic analysis and clinical correlation - Haje, Sydney Abrão; Haje, Davi de Podestá; Silva Neto, Moacir; Cassia, Guilherme de Souza e; Batista, Rodrigo Coimbra; Oliveira, Gustavo Reis Alves de; Mundim, Tito Lívio (Skeletal radiology, 2010)
Objective To assess, with computed tomography (CT) studies, features of anterior chest wall development that can be related to different types of pectus deformities. Materials and methods From 71 patients with pectus deformities and chest coronal CT scans, 48 (40 male and 8 female), with a mean age of 15.8 years (ranging from 5 years to 38.4 years) were selected and divided into five groups, according to clinical type of deformity and image quality. A similar CT study was performed in a sixth group of 14 individuals with no underlying pectus deformity (control group), six male and eight female, mean age 19.3 years, (range 10.8 years to 30.5 years), totaling 62 subjects. Tomographic studies were performed on a 64-section CT scanner, with parameters varied according to the subject’s body mass index (BMI). Coronal reconstructions were used to assess six features of the sternum and costal cartilages in the groups. Two other factors, a sternal index, created to estimate the sternal body width, and the sternocostal angles, were also studied. Results Feature I was noted in 13 patients and in no controls ( P = 0.002), feature II in 39 patients and in one control ( P = 0.000), feature III in 37 patients and in two controls ( P = 0.002), and feature IV in two patients and in no controls ( P = 0.002). The sternal index was significant to one group of patients. Conclusion The features studied and the index provide measurable and applicable data for the interpretation of anterior chest wall tomography, with possible implications for prognosis and treatment of different types of pectus deformities.